Association of sleep quality, pain severity, and depression in patients undergoing maintenance hemodialysis - Daniel Anila Roy, Uday Venkat Mateti, Pradeep Shenoy, B. C. Srinidhi (Journal of Applied Pharmaceutical Science, 2020)
Previously conducted studies state that hemodialysis (HD) patients are vulnerable to pain, depression, and insomnia. However, none of the studies have conducted the association between sleep problems, pain severity, and depression among HD patients. A cross-sectional study was conducted in the HD center of a charitable hospital for a period of 6 months to assess the prevalence of sleep problems, pain severity, and depression among patients undergoing maintenance HD and to study the association between sleep quality, pain severity, and depression in patients undergoing maintenance HD. Sleep problems, pain severity, and depression were assessed using Pittsburgh Sleep Quality Index, Beck Depression Inventory, and Visual Analog Scale questionnaires, respectively. The results showed that among the 60 patients enrolled, a majority of the subjects were male (80%) and most of them belonged to the age group of 45–64 years (63.33%). The most common comorbidity was hypertension, followed by diabetes mellitus and ischemic heart disease. Among the enrolled subjects, majority had mild pain (78.33%), poor sleep quality (78.33%), and moderate depression (43.33%). The study concludes that pain severity and depression (p-0.037), and depression and sleep quality (p-0.000) are significantly correlated among HD patients. There is a significant association between the duration of HD, sleep quality (0.000), and depression (0.002).
Keywords: Pain, depression, sleep, hemodialysis.